Identification and analysis of prognostic ion homeostasis characteristics in kidney renal clear cell carcinoma - Xiangmin Zhang; Xiongxian Qian; Yong Zhao; Maofei Ye; Liyang Li; Jian Chu (Heliyon)
Kidney renal clear cell carcinoma (KIRC), a prevalent primary malignant tumor within the urinary system, is characterized by significant heterogeneity. It has been shown that ion channels are important targets for anti-tumor therapy. In this study, we screened 70 selected KIRC related ion homeostasis genes with significant differential expression. We established diagnostic and prognostic models for 15 genes (PDK4, JPH4, ATP1A3, CCL7, CYP27B1, ABCB6, TNFSF11, MCHR1, TNNI3, ANGPTL3, Ednrb, SAA1, Chrna9, TMPRSS6, CCL14) by LASSO regression in the TCGA-KIRC cohort. We also provided a nomogram based on ion homeostasis for clinicians to explore the combined effect of the risk model on clinical variables. Patients in the low-risk group have a significant survival advantage. The potential clinical benefit of our predicted 15 gene signatures in clinical strategies was validated by Calibration Curves and DCA curves. Ultimately, the immune microenvironment and enrichment pathways were analyzed among individuals categorized as high-risk and low-risk. The predictable ion homeostasis-associated 15 gene signature established in this study predicts overall survival outcomes in patients with KIRC, to some extent helping clinicians to select personalized treatment regimens.